Neuroretinitis et causa Ocular Syphillis Vision Recovery after Multidisciplinary Management: Case Report: Poster Presentation - Case Report - Resident - RANDY VINCENT SUHARTONO KINDANGEN; Dr. dr. Made Susiyanti, SpM(K) (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Ocular syphilis is a sight-threatening condition caused by spirochete infection, Treponema pallidum, with varied clinical presentations. Although uncommon, human immunodeficiency virus (HIV) infection increases the risk of ocular syphilis. If left untreated, it may lead to blindness. The disease can be treated effectively with appropriate antibiotic therapy from a multidisciplinary department. Therefore, early investigation and timely management can prevent infection progression and save patients’ eyesight. Case Illustration : A 29-year-old man complained of blurry vision with visual acuity light perception in both eyes one month before admission. The patient underwent examination and laboratory workup and was later diagnosed with HIV and ocular syphilis. A multidisciplinary approach was carried out with dermato- venerology, neurology, and internal medicine departments to treat the ocular and systemic infection. The patient was medicated with the antibiotic regimens Benzathine Penicillin 7.2 million IU and Ceftriaxone 1 g for 14 days. Visual acuity was later examined three weeks with a significant result for best corrected visual acuity (BCVA) in decimal 0.8 for the right eye and 0.67 for the left eye. Discussion : The patient was in poor eyesight condition when initially examined. According to reports, syphilis could be cured if it was diagnosed early and completely treated. Therefore, an immediately established diagnosis helped the patient get suitable therapy thus improving visual acuity. Conclusion : Early investigation and proper treatment are critical to managing systemic and ocular infections of HIV and syphilis. A multidisciplinary approach is required to achieve optimal results.